2019
DOI: 10.1111/cas.13968
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assay for the molecular profiling of cancer by target enrichment from formalin‐fixed paraffin‐embedded specimens

Abstract: Tumor molecular profiling is becoming a standard of care for patients with cancer, but the optimal platform for cancer sequencing remains undetermined. We established a comprehensive assay, the Todai OncoPanel ( TOP ), which consists of DNA and RNA hybridization capture‐based next‐generation sequencing panels. A novel method for target enrichment, named the junction capture method, was developed for the RNA panel to acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 47 publications
(71 reference statements)
1
67
0
Order By: Relevance
“…Although current standard clinical practice does not support the routine use of genomic/transcriptomic testing in early-stage, reliable prognostic biomarkers may be helpful to select patients who are at high-risk of recurrence and who might benefit from additional systemic therapies. We have indeed included the three genes in the clinical RNA sequencing panel that we designed 49 and plan to investigate their utility to guide decisions on adjuvant systemic therapy in a prospective LUAD cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although current standard clinical practice does not support the routine use of genomic/transcriptomic testing in early-stage, reliable prognostic biomarkers may be helpful to select patients who are at high-risk of recurrence and who might benefit from additional systemic therapies. We have indeed included the three genes in the clinical RNA sequencing panel that we designed 49 and plan to investigate their utility to guide decisions on adjuvant systemic therapy in a prospective LUAD cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NGS analysis using DNA, RNA analysis allows robust detection of fusion transcripts and exon skipping . We have shown that small biopsy samples are feasible for targeted NGS analysis using RNA extracted from FFPE samples.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted sequencing is considered superior to whole genome or whole exome sequencing in the clinical setting because of higher accuracy and lower costs . From the perspective of the sequencing laboratory, samples are ideally obtained through surgical resection to analyze sufficient amounts of tumor cells and correctly call mutations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CNVs could directly in uence gene expression and have drastic phenotypic consequences due to altering gene dosage or disrupting coding sequences. [23,24]. This work discovered that ampli cation was the main type of POLR2K change and POLR2K copy number was augmented, which was related to poor survival including overall survival (OS) and disease-free survival (DFS) ( Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 99%